2014
DOI: 10.1007/s00127-014-0953-6
|View full text |Cite
|
Sign up to set email alerts
|

The journey to psychosis: an exploration of specific psychological pathways

Abstract: Recent models of psychosis have implicated specific psychological processes in the aetiology of this disorder, and these factors may form a route to later symptoms-either directly or via a mediating pathway after exposure to adversity. Researchers are beginning to bring together findings that look into specific pathways between early experiences of adversity and different symptoms of psychosis, including thought disorder, hallucinations and persecutory delusions. The adversity-specific pathways include parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…bullying). Informed by previous reviews, which suggested possible moderators and mediators of the CA psychosis relationship (Ayhan et al, 2016;Beards & Fisher, 2014;Bebbington, 2015;Freeman & Garety, 2014;Parakh & Basu, 2013;Pelayo-Teran et al, 2012;Rafiq et al, 2018;Uher, 2014;van Winkel et al, 2013;van Zelst, 2008), we will investigate the effect of genetic vulnerabilities, and biopsychosocial risk factors (e.g. substance use, adult life events and prolonged social stress), as well as psychological mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…bullying). Informed by previous reviews, which suggested possible moderators and mediators of the CA psychosis relationship (Ayhan et al, 2016;Beards & Fisher, 2014;Bebbington, 2015;Freeman & Garety, 2014;Parakh & Basu, 2013;Pelayo-Teran et al, 2012;Rafiq et al, 2018;Uher, 2014;van Winkel et al, 2013;van Zelst, 2008), we will investigate the effect of genetic vulnerabilities, and biopsychosocial risk factors (e.g. substance use, adult life events and prolonged social stress), as well as psychological mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood adversity is one environmental exposure that has been widely investigated and shown to be a robust risk factor for schizophrenic phenomenology across a spectrum of severity ranging from schizotypy personality traits to full-blown psychotic disorder [ 8 10 ]. In light of this evidence, growing attention is being focused upon elucidating whether particular adverse experiences may contribute to the development of specific symptom domains as well as the mechanistic processes involved [ 11 13 ]. These issues are relevant for informing etiological models of symptom formation and may assist the development of prophylactic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this evidence, growing attention is being focused upon elucidating whether particular adverse experiences may contribute to the development of specific symptom domains as well as the mechanistic processes involved [11][12][13]. These issues are relevant for informing etiological models of symptom formation and may assist the development of prophylactic interventions.…”
Section: Introductionmentioning
confidence: 99%